A Study on Nano Semiconductors and Its Use: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The aim of the study is to know about the nano semiconductors and its use. Semiconductors are characterized by a composition-dependent band gap energy (Eg), which is the minimum energy required to excite an electron from the ground state valence energy band into the vacant conduction energy band. With the absorption of a photon of energy greater than Eg, the excitation of an electron leaves an orbital hole in the valence band. The negatively charged electron and positively charged hole may be mobilized in the presence of an electric field to yield a current, but their lowest energy state is an electro statically bound electron-hole pair, known as the exciton. Relaxation of the excited electron back to the valence band annihilates the exciton and may be accompanied by the emission of a photon, a process known as radiative recombination.